Actual competition issues in tendering - L. F. Gataulina (Сибирское юридическое обозрение, 2014)
The article deals with the analysis of such a medium of contract conclusion as its conclusion in the tenders. The author points out the advantages of this means based on the usage of competition mechanism and participants contentiousness with the aim to achieve the most beneficial results. The article deals also with the research of the Federal law № FL-44, issued in April 5, 2013 “On the contract system in the sphere of goods purchasing, labor, services for provision of state and municipal needs” which brings forward considerable changes both in the activity of state and municipal customers concerning the organization and commodities purchasing and in the activity of state commodities purchasers.